STUDENTS’ SELF-EDUCATION IN THE CONTEXT OF THE MODERN INFORMATION SOCIETY - S. A. Asranov (Sciental Journals Publishing, 2025)
This article discusses the role and significance of students' self-education in the context of the modern information society. It is noted that the rapid development of digital technologies and access to global information resources create favorable conditions for the independent acquisition of knowledge. Particular attention is paid to motivational aspects, the difficulties students face in the process of self-education, and ways to overcome them. The importance of developing digital literacy, critical thinking skills, and self-discipline is emphasized. Self-education is considered an essential tool for preparing students for successful professional and personal fulfillment in a constantly changing world requiring continuous knowledge renewal.
Keywords: Self-education, society, motivation, thinking, process.